2021
DOI: 10.1039/d0tc04304d
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of phase stability and optoelectronic performance of BiFeO3thin filmsviacation co-substitution

Abstract: Compositional engineering of BiFeO3 can significantly boost its photovoltaic performance. Therefore, controlling site substitution and understanding how it affects the optical and electronic properties while achieving robust and stable phases...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…3). Estimates shown that for bismuth ferrite films obtained in argon and oxygen atmosphere in the initial state, the optical width of the forbidden band is about 2.7 eV, and after heat treatment in air at 550 • C for 60 minabout 2.3 eV, which is in the range of values given in the literature for oxide perovskites based on BiFeO 3 [27,28].…”
Section: Optical Properties Of Bismuth Ferrite Thin Filmssupporting
confidence: 60%
“…3). Estimates shown that for bismuth ferrite films obtained in argon and oxygen atmosphere in the initial state, the optical width of the forbidden band is about 2.7 eV, and after heat treatment in air at 550 • C for 60 minabout 2.3 eV, which is in the range of values given in the literature for oxide perovskites based on BiFeO 3 [27,28].…”
Section: Optical Properties Of Bismuth Ferrite Thin Filmssupporting
confidence: 60%
“…The 60 nm BiFeO 3 film on LSMO buffered SrTiO 3 (001) substrate, described in the Supporting Information, was grown by chemical solution deposition. 51,52 Top Pt electrodes (20 nm thick, 55 μm in diameter) were deposited by sputtering through a stencil mask. Piezoelectric Force Microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…83 Additions of 10% of lanthanum nitrate in BFCO precursor solution ensured the formation of reproducible epitaxial and pure phase La-BFCO films preserving the optical band gap and the ferroelectric properties. 79 X-ray absorption spectroscopy analysis supported by density functional theory revealed that the hybridization between Co 3d and O 2p determines the change in the optical bandgap being narrower with the coexistence of Co 2+ and Co 3+ oxidation states. The incorporation of La 3+ did not affect the electronic structure or the optical properties (see Fig.…”
Section: Complex Oxides On Rigid Substratesmentioning
confidence: 97%